Australian exercise physiology student attitudes and knowledge towards people living with mental illness. Issue 4 (16th July 2020) - Fibbins, Hamish; Ward, Philip; Stanton, Robert; Thom, Jeanette; Burdett, Amanda; Lederman, Oscar; Rosenbaum, Simon
Abstract : Purpose: Physical activity is increasingly recognised as critical to improving physical and mental health (MH). Understanding the education and training requirements of exercise professionals will support better integration of these emerging MH professionals within the multidisciplinary MH team. The purpose of this study was to determine the exposure to, knowledge and attitudes of final year exercise physiology students towards people with mental illness (MI). Design/methodology/approach: Student exposure to and knowledge and attitudes of people living with MH were assessed via a 24-item online questionnaire. Findings: In total, n = 63 out of 78 eligible students participated (81%). Of the participants, 81% ( n = 51) showed a favourable attitude towards people with MI and 68% ( n = 43) of participants had good knowledge of topics relating to MI. Significant correlations existed between the total score for attitude and any exposure to MH issues and having undertaken placement as part of university training and knowledge and total scores. Further training and education are needed to better equip exercise physiology graduates to work with people with MI. Originality/value: This is the first study to examine the attitudes and knowledge of exercise physiology students towards people living with MI and their association with exposure to MI. Given the growing number of exercise professionals being integrated into multidisciplinary MH teams, this study may help to direct the delivery of associated training and education services.